Gender and leadership issues (a study on student organizations in higher education in tasikmalaya city) - Yus Darusman; Nurlaila Nurlaila; Mumu Mumu; Ahmad Hamdan; Bilqis Damai Nuraini Megantara; Alfitriani Aulia (JETL (Journal of Education, Teaching and Learning), 2025)
Intra-campus student organizations are one way for students to develop their abilities outside the classroom, but sometimes there is a gender imbalance in the implementation of organizational leadership. The purpose of this study is to determine and analyze gender issues and leadership of intra-campus student organizations in Tasikmalaya City universities. The research method used is quantitative with survey method. The data collection techniques used were questionnaires and observations. The results of this study indicate that 56% of respondents believe that good support and facilities from student organizations can help someone to develop themselves in a better direction and 40% of respondents agree that in determining organizational leaders, it should be seen based on ability not based on gender stereotypes. But aside from this, there are obstacles and challenges that occur for women to become leaders, namely due to internal factors, these factors include women prioritizing feelings, not having the confidence to become a leader, and more burdens and responsibilities compared to men. From the results of the research that has been obtained, researchers can conclude that in reality gender and leadership issues in intra-campus student organizations in Tasikmalaya City are still minimal women who become leaders and still dominate men who become leaders, this is due to the obstacles and challenges that occur to women. But aside from this, the ideology of the respondents has begun to modernize, which means that their perspective has begun to be egalitarian and reject the idea that one must be more dominant